1999
DOI: 10.1523/jneurosci.19-11-04238.1999
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine: a Mediator of Interleukin-1β-Induced Hippocampal Synaptic Inhibition

Abstract: Interleukin-1 (IL-1) is a pleotrophic cytokine implicated in a variety of central activities, including fever, sleep, ischemic injury, and neuromodulatory responses, such as neuroimmune, and neuroendocrine interactions. Although accumulating evidence is available regarding the expression pattern of this cytokine, its receptors in the CNS, and its mechanistic profile under pathological levels, it is unclear whether this substance modulates central neurons under physiological concentrations. Further, in light of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 63 publications
3
44
1
Order By: Relevance
“…Finally, and perhaps most relevant to the endogenous LTD issue, Ikegaya et al (2003) reported that IL-1b administration rapidly produced an LTD-like suppression of synaptic transmission in CA1, in vitro. Thus, the basis of the LTD-like effects observed by Garcia et al (1998b), as well as the novelty-induced depotentiation of LTP (Xu et al, 1998a;Manahan-Vaughan and Braunewell, 1999;Abraham et al, 2002;Straube et al, 2003;Kemp and Manahan-Vaughan, 2004) may involve an IL-1b-mediated reduction of glutamate release and enhancement of adenosinemediated inhibition in the hippocampus (Murray et al, 1997;Luk et al, 1999;Kelly et al, 2003).…”
Section: Does Stress Induce An Endogenous Form Of Ltd/depotentiation?mentioning
confidence: 99%
“…Finally, and perhaps most relevant to the endogenous LTD issue, Ikegaya et al (2003) reported that IL-1b administration rapidly produced an LTD-like suppression of synaptic transmission in CA1, in vitro. Thus, the basis of the LTD-like effects observed by Garcia et al (1998b), as well as the novelty-induced depotentiation of LTP (Xu et al, 1998a;Manahan-Vaughan and Braunewell, 1999;Abraham et al, 2002;Straube et al, 2003;Kemp and Manahan-Vaughan, 2004) may involve an IL-1b-mediated reduction of glutamate release and enhancement of adenosinemediated inhibition in the hippocampus (Murray et al, 1997;Luk et al, 1999;Kelly et al, 2003).…”
Section: Does Stress Induce An Endogenous Form Of Ltd/depotentiation?mentioning
confidence: 99%
“…56,65,66 As described below, these and other inflammatory cytokines can act as somnogens, indicating a major but incompletely understood connection between the immune system and sleep. 4,16,29,31,36,[67][68][69][70][71][72][73][74][75][76][77][78][79] Another potent endogenous somnogen is the PGD 2 prostaglandin, which preferentially induces NREM sleep. 11,28,80,81 The somnogenic activity of PGD 2 is mediated at least in part by the ability of brain-produced PGD 2 to increase the concentration of extracellular adenosine.…”
Section: Introductionmentioning
confidence: 99%
“…GABA terminals are abundant in areas containing thermosensitive neurons, and muscimol application causes reductions in both firing rate and thermo-sensitivity. IL-1b and other cytokines have been shown to influence signaling with many neurotransmitters, including norepinephrine, serotonin, GABA, acetylcholine, and adenosine (14,15). The balance between these cytokines influences the level of fever and could therefore play a role in the pathogenesis of FSs.…”
Section: Introductionmentioning
confidence: 99%